2005
DOI: 10.1021/ic049251p
|View full text |Cite
|
Sign up to set email alerts
|

Structural Variety and Magnetic Properties of Tetranuclear Nickel(II) Complexes with a Central μ4-Azide

Abstract: Using a set of pyrazolate-based dinucleating ligands with thioether sidearms and a set of different carboxylates, seven tetranuclear nickel(II) complexes of types [L2Ni4(N3)3(O2CR)2](ClO4) (1) and [L2Ni4(N3)(O2CR)4](ClO4) (2) featuring an unprecedented central mu4-1,1,3,3-azide could be isolated and fully characterized. X-ray crystal structures are discussed for 1a,b,e and 2b. The mu4-1,1,3,3-azide is symmetric in all cases except 1a but exhibits distinct binding modes with significantly different Ni-N(azide)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
65
0
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 105 publications
(69 citation statements)
references
References 45 publications
0
65
0
4
Order By: Relevance
“…Synthesis and structural characterization of the complexes: We have previously shown that pyrazolate-based bimetallic complexes with accessible coordination sites can serve as suitable building blocks for the assembly of polynuclear [11,17] aggregates or 1D extendedchain compounds with alternating bridges. [19,20] The first example (2 a) of the new type 2 tetranuclear complexes was obtained serendipitously when we set out to assemble a 1D alternating chain from dinickel(ii) building blocks [L 1 Ni 2 (OAc)] 2 + , which was anticipated to occur upon replacement of the labile acetone ligands in 1 [21] by potentially bridging azide ions (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Synthesis and structural characterization of the complexes: We have previously shown that pyrazolate-based bimetallic complexes with accessible coordination sites can serve as suitable building blocks for the assembly of polynuclear [11,17] aggregates or 1D extendedchain compounds with alternating bridges. [19,20] The first example (2 a) of the new type 2 tetranuclear complexes was obtained serendipitously when we set out to assemble a 1D alternating chain from dinickel(ii) building blocks [L 1 Ni 2 (OAc)] 2 + , which was anticipated to occur upon replacement of the labile acetone ligands in 1 [21] by potentially bridging azide ions (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…Further experiments revealed that various type 2 complexes can be prepared directly from appropriate amounts of the respective components (Scheme 2). Pyrazolate-based ligands with different thioether substituents (L 1 : R = Et; L 2 : R = iPr) [17,22] as well as different carboxylates have been used in order to evaluate the scope of these systems.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations